The Political Nature of International Terrorism - J. V. Berladir; I. K. Kharichkin (Евразийская интеграция: экономика, право, политика, 2022)
This study focuses on identifying the nature of international terrorism as an extremely negative phenomenon of modern politics, as well as on defining such terms as “international terrorism” and “terrorism”.Aim. The study aims at identifying the origins of both domestic and international terrorism, and also at proposing the definitions of these political phenomena.Tasks. The tasks of this study are to identify the social-political sources of terrorism; to define the core features of this phenomenon; to propose the definitions of the terms “terrorism” and “international terrorism” based only on the core features of these notions; to propose the methods of fighting this extremely negative phenomenon of international political life.Methods. The methodology of the study is based on the recognition of the fact that the phenomenon of terrorism has a significant influence on political processes. Such a method as the comparative analysis was used in the study. The references applied in the study have content coherence with the political approach towards the understanding of terrorism. This study also addresses the cases of the successful fights against this phenomenon that can be used as examples for altering priority areas of fighting terrorism and international terrorism.Results. The study proposes the definitions of such political phenomena as “terrorism” and “international terrorism”, identifies the political nature of international terrorism. The study shows that international terrorism is a phenomenon of the same nature as domestic terrorism. The main object of both terrorism and international terrorism is a specific state, a group of states, or international organizations. To effectively fight terrorism, states need to resort to tactics of social and political maneuvering, that is to reduce the proportion of the population living below or near the poverty line, to provide the population and especially young citizens of the country with access to social mobility, and to include opposition political movements in the political process. Implementation of such measures will lead to the disappearance of the social base of terrorist organizations that will lead to the elimination of this phenomenon.Conclusion. The fight against international terrorism is being waged by individual states and the world community with mixed success. And the more states and international organisations focus on eradication of the sources of terrorism, the more successful the fight against this phenomenon will be. By extracting only the core features of terrorism and international terrorism, the universal definitions of the terms of these phenomena of political life can be developed.